Quantifying usability prioritization using K-means clustering algorithm on hybrid metric features for MAR learning - Lim K.C.; Selamat A.; Mohamed Zabil M.H.; Selamat M.H.; Alias R.A.; Puteh F.; Mohamed F.; Krejcar O. (IOS Press, 2023)
Augmented reality; Learning algorithms; Machine learning; Usability engineering; Between clusters; Mobile augmented reality; Prioritization; Prioritization techniques; Unsupervised machine learning; Usability; K-means clustering